Circular Economy in Bulgaria – Perspectives and Challenges - Ivanova, Vania (Research Papers, 2020)
The objective of this paper is to outline the state and outlooks of development of circular economy in Bulgaria, as well as demonstrate the need for adequate measures on part of public authorities to encourage this change. The research is based on a primary survey of Bulgarian employers’ attitudes towards pursuing a corporate policy relating to the principles of sustainable development, which was conducted among 200 enterprises. The analysis reveals untapped potential not only with regard to a more efficient use of resources, in both the private and public sectors, but also in terms of underestimating the significance of the issue.
Keywords: Sustainable development; Eco-fiscal policy; Ecological transformation; Circular economy; Waste management; Energy efficiency